2015
DOI: 10.1016/j.jpor.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A review of improved fixation methods for dental implants. Part I: Surface optimization for rapid osseointegration

Abstract: Besides the fundamental requirements, such as the promotion of osteogenic differentiation, the titanium implant surface should accelerate wound-healing phenomena prior to bone ingrowth toward the surface. Moreover, because initial bacterial attachment to the implant surface is unavoidable, infection control by surface modification is also an important determinant in reducing surgical failure. A desirable surface-biological relationship often needs to be characterized at the nanoscale by means of advanced techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 105 publications
0
81
0
2
Order By: Relevance
“…The outcomes of the mechanical marrow ablation model are reproducible and applicable to the study of intramembranous bone regeneration 3,4,16 and bone-implant fixation in orthopedic 9,18,19 and dental 22,23 applications. As a technique with a bone regeneration end point (Figure 4), the marrow ablation model induces trabecular bone formation within the intramedullary canal in regions that, under normal conditions, lack trabecular bone.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The outcomes of the mechanical marrow ablation model are reproducible and applicable to the study of intramembranous bone regeneration 3,4,16 and bone-implant fixation in orthopedic 9,18,19 and dental 22,23 applications. As a technique with a bone regeneration end point (Figure 4), the marrow ablation model induces trabecular bone formation within the intramedullary canal in regions that, under normal conditions, lack trabecular bone.…”
Section: Discussionmentioning
confidence: 96%
“…The marrow ablation model is primarily used for two main purposes: (1) as a model for intramembranous bone regeneration 3,4,16,17 and (2) as a model to study implant fixation in orthopedics 9,[18][19][20][21] and dentistry. 22,23 Therefore, the model is of interest to orthopedic and dental research, including biomaterial specialists, implant designers and molecular biologists as well as the field of regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the topography of the implant promotes contact between cell components and molecular bio-guests and the surface of the implant during osseointegration [2,16,17,18]. According to J. Sternad [9,10,13,19,20], roughness, surface chemistry and surface treatment of implants has a great impact on the bone-implant interface. Many current research focuses on changes of surface topography of implant materials to improve osseointegration [2,3,18].…”
Section: Discussion:-mentioning
confidence: 99%
“…The exact role of the surface topography of implants on the early stages of osseointegration of dental implants remains poorly understood. In addition, comparative clinical studies with different implant surfaces are rarely performed [13,20]. The originality of this study is that it is carried by two types of studies in vitro and in vivo for the first assessment biorectivity and cytotoxicity of titanium alloy implants (Ti6A14V), which pose still some problems osseointegration and then to improve osseointegration of titanium alloy implants with a coating of Diamond -Like Carbon (DLC).…”
Section: Discussion:-mentioning
confidence: 99%
“…Numerous reports have demonstrated that the roughness and chemistry of implant surfaces are important factors for improving osseointegration. [18][19][20] However, few studies have compared the role of the two factors in osseointegration. In this study, we prepared four surfaces that differ in roughness and chemistry and compared the effects of these surfaces on osseointegration via an in vitro cellular study and in vivo animal experiment.…”
mentioning
confidence: 99%